The quest for human dignity in the ethics of pregnancy termination : a theological-ethical evaluation of the church's approach in Kenya - Obengo, Tom Joel (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.